Evaluation of the impact of mandibular symphysis region alterations on profile aesthetics - Elif Küçük; Mücahid Yıldırım; Emire Aybüke Erdur (Scientific Reports)
Abstract The aim of this study is to assess the perceptions of orthodontists, prosthodontists, oral and maxillofacial surgeons, dentists, patients over 18 years old undergoing orthodontic treatment, and laypersons regarding altered photographs of male and female profiles, which were modified in both sagittal and vertical dimensions within the mandibular symphysis region. A total of 180 individuals participated in this study, with 30 individuals from each of the following groups: orthodontists, prosthodontists, oral and maxillofacial surgeons, general dentists, patients undergoing orthodontic treatment, and laypersons. Male and female profile images were digitally modified using Dolphin Imaging 11.95. The chin tip position was altered in sagittal (± 2 mm and ± 4 mm forward and backward) and vertical (± 2 mm and ± 4 mm upward and downward) directions, with no modifications applied to other facial structures. Participants were given an online survey containing digitally modified profile photographs of 10 females and 10 males. They were asked to rate the aesthetic appeal of these photographs. Statistical data were collected based on the gender and socio-professional status of the participants. The profile rated as the most aesthetically pleasing was the ideal profile. The least favored profiles were those of a female with the mandibular symphysis positioned 4 mm forward in the sagittal plane and a male with the mandibular symphysis positioned 4 mm upward in the vertical plane. It is concluded that mandibular symphysis modifications have a significant impact on profile aesthetics, with gender and social factors playing a determining role in aesthetic perception. Evaluations by professional experts are characterized by a more critical approach, whereas lay individuals tend to assign higher attractiveness scores to all profiles.